Factors Affecting Central Government’s Performance Accountability in Indonesia - Erawan, I Gede; Putra, Fadillah; Sentanu, I Gede (Jurnal Bina Praja, 2021)
The literature regarding the correlation of central government spending on performance accountability and the benefits of BSC implementation on the government’s performance reporting practices are rarely discussed, especially in developing countries. Consequently, this paper aims to examine the effects of expenditure budget and BSC implementation on the Indonesian central government’s performance accountability. This research employs panel data analysis using secondary data from the central government’s assessment. The findings confirm that central government expenditure and BSC implementation significantly and positively affect performance accountability. Specifically, ministries/agencies working in financial services have higher performance accountability than ministries/agencies in politics, laws, and security affairs. Additionally, the results show that the better the education level of employees, the better performance accountability. By determining the factors that positively influence performance accountability, the central government can formulate specific policies to improve its performance.